SISTEM INFORMASI FESTIVAL DAN PENJUALAN TICKET MENGGUNAKAN METODE WATERFALL - Masya, Fajar; Ramadhan, Maulana Fachry; Leyaska, Alfathu Ive; Yasir, Muhammad Afiat (JURSIMA, 2022)
With the rapid advancement of technology at this time, it supports the speed of the information dissemination process. to create an Information System application for information on festivals and annual events throughout Indonesia, as well as promote website-based ticket sales. This website-based application is a festival information and data collection application that can be accessed using the website. This application is expected to help people find festivals or annual events during this pandemic. Analyzed using the WATERFALL method. With this website, it is hoped that it will make it easier for all of us who want to visit festivals or annual events in Indonesia. This web software is made using a simple user interface so that beginners can use it practically. The result of this research is an application for the Festival Indonesia information system website. The conclusion of this study is to make it easier to find festivals and annual events.